Maximum speed: Misconceptions of sprinting - Brown, T. D.; Vescovi, J. D. (Strength and Conditioning Journal, 2012)
Despite the research available to coaches and performance professionals, training methodology for sprinting at maximum speed is often muddled by anecdotal evidence. These approaches deviate from scientific support resulting in misdirected attempts to improve performance. This article provides scientific evidence on 3 prominent constructs in this area: (a) achieving maximum speed over short distances (<30 m), (b) role of the gastrocnemius-soleus-achilles complex in sprint performance, and (c) the phase of the sprint cycle that likely plays a dominant role in achieving maximum speed. The data presented underpins an evidence-based approach for speed training.